EFFECT OF INCREASING THE PROFITABILITY OF PRODUCTION CAPACITY IN THE BEEKEEPING - Mladenović, Mića; Orović, Dragan G.; Milosavljević, Saša M. (Economics of Agriculture, 2011)
Developed beekeeping is an important component of modern agriculture, both for the production of honey, pollen, royal jelly, propolis, beeswax and bee venom, and the pollination of plants and increase yield. Engaging bees as pollinators is increasing the quality and quantity of obtained fruits. Spontaneous and cultivated flowering plants are an irreplaceable source of natural food for honeybees, and one can reasonably talk about the perfect symbiosis of flowering plants and bees. This paper presents a natural economic and organizational conditions of production of bee products, as well as economic and agro economic signifcance. The purpose of the analysis is to identify and show the costs incurred, their value and structure during the period when the equipment is modern, and this is a period of 20 years. This work includes the analysis of the results of production, achieved yields and production volume, production value and the actual fgures, and derived indicators of business success: effciency and proftability, and payback period. All the analysis has been done to a capacity of 100, 200 and 300 beehives.